2017
DOI: 10.1038/ni.3847
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lineage-specifying cytokines that signal all CD8+-cytotoxic-lineage-fate 'decisions' in the thymus

Abstract: T cell antigen receptor (TCR) signaling in the thymus initiates positive selection but CD8 lineage fate is thought to be induced by cytokines after TCR signaling has ceased, although this remains controversial and unproven. We now identify four non-common gamma chain (γc) receptor-signaling cytokines (IL-6, IFN-γ, TSLP, TGF-β) that, like IL-7 and IL-15, induce expression of the lineage-specifying transcription factor Runx3d and signal the generation of CD8 T cells. Remarkably, elimination of in vivo signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…I-specific CD8 T cells only differentiate after a disruption of MHC class II/TCR signals and subsequent cytokine signaling. 84,85 Interestingly, in the presence of high levels of ectopic ZAP-70 from the AAV8-ZAP-70 vector (Fig 3, C), both the thymic and peripheral CD4/CD8 ratios in AAV8-ZAP-70-treated mice were significantly skewed to a CD4 lineage fate (P < .05; Figs 2, D, and 3, E).…”
Section: Intrathymic Aav8-zap-70 Transduction Promotes Long-term Mainmentioning
confidence: 92%
“…I-specific CD8 T cells only differentiate after a disruption of MHC class II/TCR signals and subsequent cytokine signaling. 84,85 Interestingly, in the presence of high levels of ectopic ZAP-70 from the AAV8-ZAP-70 vector (Fig 3, C), both the thymic and peripheral CD4/CD8 ratios in AAV8-ZAP-70-treated mice were significantly skewed to a CD4 lineage fate (P < .05; Figs 2, D, and 3, E).…”
Section: Intrathymic Aav8-zap-70 Transduction Promotes Long-term Mainmentioning
confidence: 92%
“…3C). IL-7 and TGF-b are two cytokines that are instrumental in phase 2 (31). Flow cytometry analyses revealed that 8M1 and 8M2 thymocytes from Psmb11 2/2 thymi had slightly but significantly lower levels of surface CD127 (Fig.…”
Section: Selection Of Cd8 Thymocytes Is Dysregulated In Psmb11 2/2 Thymimentioning
confidence: 97%
“…3C). In addition, a 3.5-fold downregulation in the expression of Itgae, which is specifically induced by TGF-b signaling (31), was observed in the 8SM subset from Psmb11 2/2 mice (Supplemental Table I). Overall, these data suggest that in Psmb11 2/2 thymi, CD8 thymocytes receive strong TCR signals but show evidence of impaired cytokine signaling thereafter.…”
Section: Selection Of Cd8 Thymocytes Is Dysregulated In Psmb11 2/2 Thymimentioning
confidence: 99%
“…These findings indicate that iPSC-derived T cell differentiation may require the provision of additional physiologically relevant signals. Much has been learned over the past decades about how T cells develop within the thymus, and although the signals provided within the thymic microenvironment are still incompletely elucidated, they are not limited to Notch/Delta-like ligands and TCR stimulation as currently provided to iPSCs for in vitro differentiation (Etzensperger et al, 2017; Singer et al, 2008). …”
Section: Introductionmentioning
confidence: 99%